The evolution of marginal-marine systems of the Amibberg formation, Karasburg Basin, Southern Namibia: implications for Early-Middle Permian palaeogeography in South Western Gondwana - Berti, Michael (My University, 2015)
The Karasburg Basin is situated in southern Namibia and preserves a heterogeneous succession of Karoo Supergroup strata up to 1000m thick. The uppermost preserved succession in this basin is the Amibberg Formation which is 250m thick and consists of intervals of sandstone, siltstone and mudstone. This study uses facies analysis, sequence stratigraphy and petrography to determine the palaeogeography and provenance for the Amibberg Formation. This is then used to establish environmental variability across the Karasburg – Aranos – Main Karoo basins and to define an equivalent of the Amibberg Formation in the Main Karoo Basin. Detailed stratigraphic logging of five outcrop localities has led to the identification of seven distinct lithofacies and two dominant ichnofacies (Cruziana and Skolithos). These lithofacies include: 1) Massive, laminated and bioturbated mudstones interpreted as offshore deposits (OS); 2) Bioturbated siltstones and sandstones which are representative of offshore-transitional environments (OST); 3) Interbedded sandstones and siltstones also interpreted as offshore-transitional deposits (OST) and generated by river-fed hyperpycnal plumes; 4) Sharp based, massive sandstones interpreted as being deposited on the distal lower shoreface (dLSF); 5) Non-amalgamated hummocky cross-stratified (HCS) and wave rippled sandstones interpreted as distal lower shoreface deposits (dLSF); 6) Amalgamated HCS and wave rippled sandstones interpreted as proximal lower shoreface deposits (pLSF); and 7) Soft-sediment deformed (SSD) sandstones and siltstones occurring in close juxtaposition with dLSF and pLSF deposits. The vertical arrangement of these lithofacies shows a general coarsening and shallowing upward trend. Overall the rocks of the Amibberg Formation consist of wave-dominated shoreface deposits with significant influence by tidal processes. Petrographically, the sandstone samples fall into the class of quartz and feldspathic wackes and are sourced from craton interior provenances. Geochemical analysis of mudstones and nodules indicate high levels of microbial activity under predominantly oxic conditions during the deposition of the Amibberg Formation. Five poorly defined 4th order T-R cycles are observable within the strata of the Amibberg Formation. Large regressive intervals are capped by thin transgressive tracts and these cycles are interpreted to have formed due to eustatic processes. Overall, the Amibberg Formation represents a regressive shoreline. iii Based on the mean palaeocurrent vectors a NNE-SSW palaeoshoreline orientation is deduced and the shoreface must have occupied a palaeohigh on the northern side of the western Cargonian Highlands. This emergent highland acted as an extensive headland and assisted in the connectivity of the Karasburg and Aranos basins, with partial connectivity with the Main Karoo Basin during the Early Permian. Based on this study, the Amibberg Formation is considered an equivalent of the Waterford Formation in the Main Karoo Basin based on similar: stratigraphic position; thickness; sedimentary structures; trace fossil assemblages and stacking patterns.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science. Johannesburg, 2014.
Keywords: Karasburg Basin; Amibberg Formation; Karoo Supergroup; Lithofacies; Provenance; T-R cycles; Palaeoshoreline; Cargonian Highlands; Waterford Formation; Marine sediments.; Sedimentation and deposition.; Facies (Geology); Paleogeography.